Energetic study of cardioplegic hearts under ischaemia/reperfusion and [Ca2+] changes in cardiomyocytes of guinea-pig: Mitochondrial role - Ragone, María Inés (2012)
Abstract Aim: To study the role of mitochondria in the recovery of guinea-pig hearts exposed to high-K+-cardioplegia (CPG) and ischaemia/reperfusion (I/R) Methods: We measured contractility and heat release in perfused guineapig hearts and cytosolic and mitochondrial Ca2+ by epifluorescence and confocal microscopy in isolated cardiomyocytes loaded with Fluo-4 or Rhod-2. Results: In hearts, CPG increased the postischaemic contractile recovery, and this was potentiated by the mNCX blocker clonazepam and the mKATP opener diazoxide, which also prevented the fall in muscle economy. Moreover, CPG prevented the stunning induced by ouabain, which was reduced by clonazepam. In cardiomyocytes, CPG increased fluorescent signals of cytosolic and mitochondrial Ca2+, while the addition of a mNCX blocker (CGP37157) increased cytosolic but reduced mitochondrial [Ca2+]. Ouabain in CPG increased cytosolic Ca2+ and resting heat, but the addition of CGP37157 reduced them, as well as mitochondrial Ca2+. Conclusions: CPG, diazoxide and clonazepam improve postischaemic recovery, respectively, by increasing the Ca2+ cycling and by reducing the mitochondrial Ca2+ uptake either by uniporter or by mNCX. The mitochondria compete with the leaky sarcoplasmic reticulum (SR) as sink of Ca2+ in guinea-pig hearts, affecting the postischaemic contractility. CPG also prevented the ouabain-induced dysfunction by avoiding the Ca2+ overload. Ouabain reduced the synergism between CPG and clonazepam suggesting that [Na+]i and SR load influence the mNCX role.